Dynamic hyperinflation occurs in healthy subjects during maximal voluntary ventilation - Herpeux, Audrey; Pauwen, Nathalie Y.; Sergysels, Roger; Peeters, Anneleen; Ninane, Vincent; Bruyneel, Marie (Frontiers in Medicine, 2025)
BackgroundDynamic hyperinflation (DH) commonly occurs during maximum voluntary ventilation (MVV) in obstructive lung diseases and is usually attributed to expiratory flow limitation. However, in healthy individuals, maximal effort typically remains insufficient to induce DH. This study aimed to determine whether DH can also develop during MVV in normal subjects without expiratory flow limitation, challenging the current concepts of its occurrence in physiological conditions.MethodsForty-three healthy subjects (25 males/18 females; 40–68 yrs; FEV1: 3.4 ± 0.8 L) performed MVV at increasing breathing frequencies (ranging from 10 to 100 breaths.min−1) and maximal tidal volumes. Inspiratory capacity (IC) was measured at rest and every 12 s during MVV to detect DH. When DH occurred at a certain frequency (BFDH), a single additional MVV at a higher frequency was performed to confirm its occurrence.ResultsDH occurred at or below 100 breaths.min−1 in 39 of 43 healthy subjects (91%), with the mean onset at 52 breaths.min−1. There was no significant correlation between the frequency of breathing at the onset of DH and age, body mass index, lung volumes, or flows. However, BFDH was significantly and inversely correlated with resting [IC/FVC], meaning that individuals operating at lower resting ventilatory levels reached DH at lower breath frequency (BF).ConclusionDH can occur at low and variable breathing frequencies during MVV in healthy subjects. The onset of DH may be related to the mechanical thoracopulmonary state at rest, suggesting that the baseline lung mechanics may determine the susceptibility to DH during high-intensity ventilatory maneuvers.